Exposure and toxicity of Polybrominated Diphenyl Ethers: a mini review - Navaretnam, Raneesha; Mohd Jaafar, Izazy’ Nur; Shukor, Mohd Yunus; Yasid, Nur Adeela (Hibiscus Publisher Enterprise, 2023)
Polybrominated Diphenyl Ethers (PBDEs), recognized as persistent organic pollutants by the United Nations Environment Programme, are a class of brominated flame retardants that pose significant environmental and health risks. These compounds, consisting of two aromatic rings with up to 10 bromine atom substitutions, are categorized into penta-BDE, octa-BDE, and deca-BDE based on their bromine content, each exhibiting distinct environmental behaviors. PBDEs with fewer bromine atoms are more volatile and prone to bioaccumulation, raising significant health concerns. These compounds, often added physically to products, can leach into the environment, leading to pollution during production and after the parent polymer degrades. The transformation of higher brominated diphenyl ethers into less brominated forms in the environment further complicates their impact, with mono-brominated BDE-3 being particularly concerning due to its extended atmospheric photolysis lifetime and increased bioavailability. The management of PBDEs is challenging due to their persistence and transformation in the environment. As endocrine disruptors, they are linked to various acute and chronic toxicological effects, including neurodevelopmental toxicity, teratogenicity, and potential carcinogenicity. Their structural similarity to thyroid hormones allows them to disrupt thyroid hormone balance, leading to further health complications. The subject of this review is to summarize the current body of knowledge that is essential to understand their long-term effects on ecosystems and human health and to develop strategies to mitigate their adverse impacts.